Effect of nebivolol on liver regeneration in an experimental 70% partial hepatectomy model - Fatih Sumer (Asian Journal of Surgery, 2017)
Background: Factors affecting liver regeneration are still relevant. The purpose of this study is to investigate the effect of nebivolol treatment on liver regeneration in rats in which 70% partial hepatectomy was performed. Methods: Three groups were created: the control group, the low dose group, and the high dose group, with 20 rats in each group and 70% hepatectomy was performed in all rats. Immediately after partial liver resection, 2 mL physiological saline solution was administered to the control group via oral gavage, 0.5 mg/kg nebivolol was administered via oral gavage to the low dose group and 2 mg/kg nebivolol was administered via oral gavage to the high dose group. On the 1st and 5th days after liver resection, 10 subjects were sacrificed from each group, and liver weights and the mitotic count and Ki-67 were measured. Results: Regenerating liver weight on the 1st and 5th days after partial hepatectomy was statistically different in the low dose and high dose nebivolol groups compared to the control group. Mitotic count on the 1st day after partial hepatectomy was significantly higher in the low dose and high dose nebivolol groups than the control group. There was no statistically significant difference detected between the three groups for the 5th day. On the 1st day, Ki-67 rates were significantly higher in both groups given nebivolol than the control group. However, 5th day results were not statistically significant. Conclusion: Nebivolol increases regeneration after partial hepatectomy in rats.